Life on the trail - Kalman, Bobbie (New York : Crabtree Pub., 1999)
This book describes the life and work of cowboys, including the roundup, branding, bronco bustin, and driving cattle hundreds of miles along cattle trails.
Includes index.
Keywords: Ranch life -- History -- Juvenile literature. -- 19th century -- West (U.S.); Cattle trails -- History -- Juvenile literature. -- 19th century -- West (U.S.); West (U.S.) -- Social life and customs -- Juvenile literature